Hubungan Rasio Lingkar Pinggang Panggul dengan Penderita Hipertensi pada Lansia di Wilayah Kerja Puskesmas Wire Kabupaten Tuban - Ida Nur Ariyanti; Lilia Faridatul Fauziah (Yayasan Literasi Sains Indonesia, 2024)
High blood pressure or hypertension is a public health problem in Indonesia. High blood pressure or hypertension is a condition in which blood pressure in the arteries increases consistently above normal limits. This study aims to analyze the relationship between the waist-hip circumference ratio and the incidence of hypertension in the elderly in the Wire Health Center work area of ​​Tuban Regency.This study uses an observational analytical research design with a